(untitled) (Research, Society and Development, 2020)
The use of a biomodel allows for simulation and aids in team communication, can be used as prostheses, reduces surgical time, and is a reliable copy of bone tissue. Thus, this work aims to report a clinical case of using the biomodel in orthognathic surgery, in order to demonstrate the benefits obtained with the use of biomodels in surgical planning, such as reducing time, increasing predictability, pre-modeling of titanium plates used in bone fixations. Melanoderma patient, male, sought dental care, with dissatisfaction of facial aesthetics and difficulty in phonation, chewing and breathing. After a detailed physical examination and evaluation through imaging tests, Angle skeletal classification III was identified, with indication for surgical treatment. The trans-operative was simplified and faster due to the previous model of the plates and precision of adaptation of them in the bone surface. The use of biomodels and the previous modeling of fixation plates favored greater surgical precision, through the reduction of trans-operative morbidity and reduction of surgical time. Thus, it emphasizes that this type of approach can be an important ally in the treatment of correction of dento-facial deformities. Furthermore, the knowledge of these new tools enabled a better diagnosis and surgical precision.